Impact of frailty on the long-term prognosis of the elderly with hepatocellular carcinoma treated with transarterial chemoembolization - Yu-Fei Shao; Ya-Nan Zu; Xiang-Qi Yin; Jin-Chang Xiao; Yu-Ming Gu (Scientific Reports)
Abstract Transcatheter arterial chemoembolization (TACE) is a standard treatment for unresectable, intermediate, or advanced-stage hepatocellular carcinoma (HCC), especially in elderly patients. The modified 5-item frailty index (mFI-5) is a concise, comorbidity-based risk stratification tool proven to effectively predict adverse outcomes. However, the prognostic capacity of the mFI-5 in elderly HCC patients after TACE is unclear. As such, we retrospectively analyzed clinical data from elderly HCC patients (age ≥ 65 years) who received their first TACE between November 2018 and November 2020 at the Department of Interventional Radiology, Affiliated Hospital of Xuzhou Medical University. The mFI-5 was calculated based on the presence of five co-morbidities: congestive heart failure within 30 days prior to surgery; insulin-dependent or noninsulin-dependent diabetes mellitus; chronic obstructive pulmonary disease (COPD) or pneumonia; partially dependent or totally dependent functional health status at time of surgery; and hypertension requiring medication. Patients were divided into two groups based on mFI-5 scores: mFI-5 ≥ 2 (‘frail’) and mFI-5 < 2 (‘non-frail’). The primary outcomes were overall survival (OS) and progression-free survival (PFS).Among the 143 patients, 97 were in the mFI-5 < 2 group and 46 in the mFI-5 ≥ 2 group. The median OS was 40.0 months (95% confidence interval [CI]: 35.0–47.0) in the non-frail group vs. 24.0 months (95% CI: 22-NA) in the frail group (hazard ratio [HR] = 3.343, 95% CI: 1.802–6.201, p < .001). The median PFS was 7.0 months (95% CI: 4.0–11.0) vs. 3.0 months (95% CI: 2.0–9.0) (HR = 1.507, 95% CI: 0.996–2.280, p = .053). Cox regression identified mFI-5, alpha-fetoprotein (AFP) as independent predictors of OS. The mFI-5 is a useful predictor of long-term survival in elderly HCC patients treated with TACE, suggesting that incorporating frailty assessments can optimize treatment strategies and improve outcomes.